Data structures from recipes to C - Turner, Lawrence E. (Dubuque, Iowa : W.C. Brown, 1994)
Aims to provide a sound foundation for understanding data structures, with coverage progressing from less efficient data structures to more efficient ones, and attempting to give students a sound understanding of algorithms and how they work.
Includes index.
eng.
Keywords: Data structures (Computer science); C (Computer program language)